Bentuk, Fungsi, dan Makna Interior Rumah Adat Suku Tolaki dan Suku Wolio di Sulawesi Tenggara - Laksmi Kusuma Wardani, Bonnieta Franciska (Intra, 2014)
Clans Tolaki and Wolio are two very prominent clans in Southeast Sulawesi island implement cultural value system when building a house to live in or homes to gather, the so-called cosmological natural divisions and division which refers to the body anlogi. Formation and function of the existing interior in Tolaki tribal house and tribal house Wolio is and should be maintained so that the ancestral culture does not disappear. Custom home at the time now many are not treated, so the meaning of the form and function of the interior tribes and tribal Wolio Tolaki no longer fully contain customary meaning as changes induced in ancestral times so when direkrontuksi is no such customary rules and regulations. Basics of notching custom home design and the meaning of the formation and function are the things that should be known of the two tribes and tribal tribes Tolaki Wolio through qualitative research methods. Notching custom home construction arrangement of these families is very evident in the distribution and pemaknaanya, so when building a house it seems clear that there is an analogy of the body is contained in either house of the arrangement and structure.Â